Achilles tendon repair by a minimally invasive technique using Tenolig® - Oliveira, Vinicius; Prata, Sérgio (Journal of the Foot & Ankle, 2020)
Objective: To assess the degree of postoperative satisfaction of patients with acute Achilles tendon rupture who underwent surgical reconstruction by a minimally invasive technique using Tenolig®. Methods: A retrospective observational study was conducted with 18 patients with acute Achilles tendon rupture diagnosed by a positive Thompson test who underwent surgery. Outcomes were assessed using the American arthopaedic Foot and Ankle Society (AOFAS) score and the Foot Function Index (FFI). Furthermore, quantitative variables were descriptively treated, and patients’ age was correlated with FII and AOFAS score using Spearman’s correlation coefficient at a significance level of 5%. Results: Patients underwent surgery from one to six days after injury and were discharged one day later. Only one patient had a superficial postoperative infection. Patients’ AOFAS scores ranged from 75 to 100 points, and FFI ranged from 0 to 20%. The patient with superficial postoperative infection had an AOFAS score and a FFI of 75 points and 20%, respectively. Conclusion: Percutaneous repair of complete Achilles tendon rupture with Tenolig® resulted in high functional scores and a low rate of complications. Level of Evidence IV; Therapeutic Studies; Case Series.